2020
DOI: 10.1002/lary.28964
|View full text |Cite
|
Sign up to set email alerts
|

Mood, Anxiety and Olfactory Dysfunction in COVID‐19: Evidence of Central Nervous System Involvement?

Abstract: The objective of this study was to determine the burden of depressed mood and anxiety in COVID-19, and associated disease characteristics. Materials and Methods: This is a prospective, cross-sectional study of 114 COVID-19 positive patients diagnosed using RT-PCR-based testing over a 6-week period. The two-item Patient Health Questionnaire (PHQ-2) and the two-item Generalized Anxiety Disorder questionnaire (GAD-2) were used to measure depressed mood and anxiety level, respectively, at enrollment and for partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 44 publications
5
95
1
4
Order By: Relevance
“…An Italian survey‐based study observed sleep impairment as the most commonly reported neurological symptom (94/103 patients) 73 . A prospective cross‐sectional study from the USA showed that impaired sense of smell was associated with anxiety and depressed mood 74 . Finally, a UK‐wide surveillance study recorded 23 patients with neuropsychiatric disorders, among them new‐onset psychosis (10 patients, 43%), neurocognitive syndrome (6 patients, 26%), and affective disorders (4 patients, 17%) 58 …”
Section: Resultsmentioning
confidence: 99%
“…An Italian survey‐based study observed sleep impairment as the most commonly reported neurological symptom (94/103 patients) 73 . A prospective cross‐sectional study from the USA showed that impaired sense of smell was associated with anxiety and depressed mood 74 . Finally, a UK‐wide surveillance study recorded 23 patients with neuropsychiatric disorders, among them new‐onset psychosis (10 patients, 43%), neurocognitive syndrome (6 patients, 26%), and affective disorders (4 patients, 17%) 58 …”
Section: Resultsmentioning
confidence: 99%
“…Some authors found significant associations between self-reported olfactory disorders and female gender [ 2 , 7 , 32 , 33 , 34 , 35 ], younger age [ 32 , 33 , 36 , 37 , 38 ], smoker [ 39 ] or no-smoker [ 33 ] habit, hypertension [ 15 ], diabetes [ 18 ], depression [ 40 ], or symptoms such as fever [ 2 ] and nasal obstruction [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Meini et al reported that chemosensory dysfunction was more frequent in patients requiring hospitalization because of respiratory failure [ 18 ]. Speth et al noticed that the shortness of breath was more severe in patients experiencing olfactory dysfunction [ 29 ]. Although, in this study, there was no difference between patients with and without STD in Group P in terms of shortness of breath, ‘ground-glass appearance’ was significantly more frequent in the patients with STD.…”
Section: Discussionmentioning
confidence: 99%